Construction contractors involvement in disaster management planning (Construction Economics and Building, 2014)
Disasters, both natural and man-made, cause major damage and loss of life. Because of this, governments around the world are looking at building resilience to ensure communities can recover quickly and have minimal impact from a disaster. Part of building resilience is to plan for disaster management and recovery. Literature reveals that construction contractors can play a critical role within this process as they have control of resource supply chains and key knowledge and skills they are well suited to assist in disaster planning. However, as literature also reveals there is currently little involvement of construction contractors in the disaster planning process. This gap between what should be done and what is currently done is investigated. Representatives from industry bodies are interviewed to determine their understanding of the industry’s involvement in disaster planning and what capacity the industry might have to be involved. The interviewee’s responses agree with current literature that there is currently little or no involvement with disaster planning however there is interest in being involved with disaster management planning if there was a forum for this to occur. Based on the responses the researcher has proposed a model to engage construction contractors within state government disaster management planning.